Maneuver Warfare : An Anthology - Edited By Hooker, Richard D. Jr. and Foreword By Galvin, John R. (Rawalpindi Army Education Press, 2000)
The army is in the process of losing up to one half of its combat divisions in the current downsizing. Several of the essayists in this collection suggest that a smaller army could actually be a stronger one, if it is trained and equipped to fight in the maneuver-warfare mode. William Lind opens the anthology with as clear a definition of this broad and fuzzy concept as may be possible: maneuver warfare, relying not on firepower or industrial might, emphasizes decentralized command and rapid operating tempo in applying tactical strength against the enemy's weakness. Richard Hooker explains how German tactics in WW I remain the best model for maneuver warfare. David Grossman discusses why WW II German General Erwin Rommel is thought of as a sterling maneuverist. Michael D. Wyly reveals how maneuver warfare is taught and some of its training methods. Daniel P. Bolger's amusingly skeptical essay suggests that maneuver warfare theory is "a bag of military Doritos--tasty and great fun to munch, but not very nutritious." Readers will find in this timely anthology a thorough discussion of the primary doctrine of American ground forces now and in the foreseeable future.
Include Bibliography.
Keywords: Maneuver Warfare -- Military Policy